2018
DOI: 10.3389/fimmu.2018.01114
|View full text |Cite
|
Sign up to set email alerts
|

NKp44-Derived Peptide Binds Proliferating Cell Nuclear Antigen and Mediates Tumor Cell Death

Abstract: Proliferating cell nuclear antigen (PCNA) is considered as a hub protein and is a key regulator of DNA replication, repair, cell cycle control, and apoptosis. PCNA is overexpressed in many cancer types, and PCNA overexpression is correlated with cancer virulence. Membrane-associated PCNA is a ligand for the NKp44 (NCR2) innate immune receptor. The purpose of this study was to characterize the PCNA-binding site within NKp44. We have identified NKp44-derived linear peptide (pep8), which can specifically interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Interestingly, the inhibitory form of NKp44 has been found on tumor-infiltrating NK cells, 40 and blocking the interaction NKp44-PCNA results in inhibition of tumor growth including melanoma in mouse models. 41 Hence, NCR can be considered as novel innate immune checkpoints, which, based on our results, offer an exciting potential therapeutic target to manipulate in cancer.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, the inhibitory form of NKp44 has been found on tumor-infiltrating NK cells, 40 and blocking the interaction NKp44-PCNA results in inhibition of tumor growth including melanoma in mouse models. 41 Hence, NCR can be considered as novel innate immune checkpoints, which, based on our results, offer an exciting potential therapeutic target to manipulate in cancer.…”
Section: Discussionmentioning
confidence: 78%
“…Novel NK cell checkpoint ligands expressed on cancer cells could be desirable targets for new immune checkpoint blockers with favorable toxicity profiles compared to other established immune checkpoints (171). Recently, it was demonstrated that the NKp44 isoform1 receptor, a splice variant of the activating NKp44 receptor, can bind membrane proliferating cell nuclear antigen (PCNA) upregulated on cancer cells, inhibiting NK cell activation (293,294). This is a potentially attractive target due to its different expression profile in healthy proliferating cells vs. cancer cells.…”
Section: Novel Nk Cell Inhibitory Checkpoints/tumor Antigens For Blocmentioning
confidence: 99%
“…Cytosolic roles: Multiple cytosolic proteins involved in cellular signaling and metabolism, including glycolytic enzymes, contain APIM or PIP-box motifs (Ohayon et al, 2019;Olaisen et al, 2018;Olaisen et al, 2015), or are found in complex with PCNA (Naryzhny & Lee, 2010;Olaisen et al, 2015;Witko-Sarsat et al, 2010). Studies have shown that impairing PCNA´s scaffold function affects multiple signaling pathways including the PI3K/AKT and MAPK pathways and the cytokine production after toll receptor stimuli (Olaisen et al, 2018;Olaisen et al, 2015;Sogaard et al, 2019), regulation of apoptosis (Müller et al, 2013;Witko-Sarsat et al, 2010;Yin et al, 2015), cytotoxicity of NK cells (Rosental et al, 2011;Shemesh et al, 2018), and cellular defense against ROS (Ohayon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%